Polyester-based adhesive composition, polyester-based adhesive, adhesive sheet, and optical member with adhesive layer
By using a composition of a polyester-based resin with a glass transition temperature of -20 to +30°C and a hydrolysis inhibitor, the problem of insufficient adhesion and foam resistance in a high temperature and high humidity environment is solved, and efficient adhesion and durability are achieved.
Patent Information
- Application Number
- CN202411668244.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2017-12-04
- Filing Date
- 2017-12-27
- Publication Date
- 2025-03-07
AI Technical Summary
The existing polyester-based adhesives show low adhesion and poor foam resistance in high temperature and high humidity environments, which cannot meet the market's demand for high-level foam resistance.
The polyester resin with a glass transition temperature of -20 to +30°C and a hydrolysis inhibitor composition are used to improve the heat and moisture resistance of the adhesive by using a specific resin composition and a crosslinking agent.
It realizes the high level of foam resistance and adhesion in high temperature and high humidity environments, and is suitable for the adhesion of optical components, especially optical components formed by plastic materials.
Smart Images

Figure BDA0005145134830000251 
Figure BDA0005145134830000281 
Figure BDA0005145134830000311
Abstract
Description
[0001] The present application is a divisional application of an application filed on December 27, 2017, with application number 201780080441.9 and invention name “Polyester-based adhesive composition, polyester-based adhesive, adhesive sheet and optical member with adhesive layer”. Technical Field
[0002] The present invention relates to a polyester-based adhesive composition, a polyester-based adhesive, an adhesive sheet, and an optical member with an adhesive layer using the same. Background Art
[0003] In the past, polyester resins have excellent heat resistance, chemical resistance, durability and mechanical strength, and therefore have been used in a wide range of applications such as films, plastic bottles, fibers, toners, motor parts, adhesives, and pressure-sensitive adhesives. In recent years, polyester pressure-sensitive adhesives have been increasingly used as pressure-sensitive adhesives for bonding optical components.
[0004] On the other hand, in recent years, display devices such as liquid crystal displays (LCDs) and input devices such as touch panels used in combination with the above-mentioned display devices have become increasingly widely used in various fields. In their manufacture, transparent adhesive sheets, such as double-sided adhesive sheets without substrates, are used in the pasting of optical components such as optical films and substrates.
[0005] Here, the optical components that constitute optical devices such as touch panels require a transparent substrate. In the past, glass substrates such as glass protective covers and glass substrates have been used. However, in recent years, from the perspective of impact resistance and lightweight, plastic substrates such as polycarbonate resins, acrylic resins, and (cyclic) olefin resins have gradually been used to replace glass substrates.
[0006] However, when such a plastic substrate is used, there is a problem that bubbles and peeling occur between the plastic substrate and the pressure-sensitive adhesive layer due to gas and moisture generated from the plastic substrate, thereby causing a decrease in visibility.
[0007] Therefore, the pressure-sensitive adhesive used for bonding optical members is required to have a performance that can suppress the foaming and peeling thereof (hereinafter referred to as foaming resistance).
[0008] For example, Patent Document 1 describes an adhesive comprising a polyester resin having a number average molecular weight of 5,000 or more as an adhesive that can be used in a wide range of applications and that exhibits sufficient adhesive force with pressure at the level of finger pressure, has excellent adhesion, heat resistance, and mechanical strength. The adhesive is obtained by polycondensing a carboxylic acid component comprising 10 mol % or more and less than 50 mol % of an aromatic dicarboxylic acid and a polyol component comprising 5 mol % or more of a diol having a hydrocarbon group in a side chain, and contains a polyester resin having a number average molecular weight of 5,000 or more. It is also described that the adhesive can be used as an adhesive for optical components.
[0009] In addition, Patent Document 2 describes a pressure-sensitive adhesive composition as an adhesive composition that has excellent surface adhesion, adhesion, heat resistance, moisture resistance, creep resistance and other properties both initially and after heat and humidity aging, and can form an excellent adhesive layer. The pressure-sensitive adhesive composition is characterized in that it comprises: a polyester resin having a glass transition temperature in the range of -80 to 0°C, having hydroxyl and / or carboxyl groups in the side chains, and containing 5 to 50 mol% of an aromatic ring structure; a cyclic diterpene compound; and a reactive compound that can react with the hydroxyl and / or carboxyl groups in the aforementioned resin.
[0010] Furthermore, Patent Document 3 describes a polyester-based adhesive composition as a polyester-based adhesive composition that can achieve both durability (storability under heating and humidification) and adhesive properties, which is characterized in that it contains polyester, an anti-hydrolysis agent, a tackifier and a cross-linking agent, the acid value of the tackifier being 8 or less, the softening point of the tackifier being 80 to 170°C, and the amount of the tackifier being 20 to 100 parts by weight relative to 100 parts by weight of the polyester.
[0011] Prior art literature
[0012] Patent Literature
[0013] Patent Document 1: Japanese Patent Application Publication No. 2007-45914
[0014] Patent Document 2: Japanese Patent Application Publication No. 2009-7419
[0015] Patent Document 3: Japanese Patent Application Publication No. 2015-134906 Summary of the invention
[0016] Problem that the invention aims to solve
[0017] However, the adhesive described in Patent Document 1 utilizes a polyester resin containing a polycarboxylic acid component having a low content of aromatic dicarboxylic acid. Therefore, the glass transition temperature of the polyester resin is low, and the adhesive strength tends to decrease at high temperatures (particularly above 80° C.), and the blistering resistance under high temperature and high humidity conditions is poor.
[0018] Furthermore, the adhesive actually disclosed in Patent Document 2 also uses a polyester resin having a low glass transition temperature, and has insufficient adhesive strength under high temperature and high humidity conditions, and cannot achieve a high level of blister resistance required by the market.
[0019] Furthermore, according to the research of the present inventors, the glass transition temperature of the polyester-based adhesive composition described in Patent Document 3 is about -50°C, and the adhesive force of the adhesive tape actually disclosed is insufficient, and the high level of blister resistance required by the market cannot be obtained.
[0020] The present invention has been made in view of the above-mentioned conventional actual situation, and an object of the present invention is to provide a polyester-based adhesive composition capable of obtaining an adhesive having a high level of blister resistance even when exposed to a high-temperature and high-humidity environment.
[0021] Solutions for solving problems
[0022] In view of the above situation, the present inventors have repeatedly conducted intensive studies and found that, in a polyester-based adhesive composition, by using a polyester-based resin (I) having a glass transition temperature in a specific range higher than that of resins generally used in adhesive compositions, an adhesive having a very high level of blister resistance can be obtained, thereby completing the present invention.
[0023] That is, the present invention relates to the following <1> to <13>.
[0024] <1> A polyester adhesive composition, characterized in that it contains a polyester resin (I) and a hydrolysis inhibitor (II),
[0025] The polyester resin (I) is a polyester resin (I-α) having a glass transition temperature of -20 to +30°C.
[0026] <2> A polyester adhesive composition, characterized in that it contains a polyester resin (I),
[0027] The aforementioned polyester resin (I) is a polyester resin (I-β) having a glass transition temperature of -20 to +30°C, and is obtained from a polycarboxylic acid component (A) containing an aromatic dicarboxylic acid (a1) at a content ratio of 50 mol% or more, and a polyol component (B) containing a diol compound (b1) having a hydrocarbon group in a side chain, wherein the content ratio of isophthalic acid relative to the entire aromatic dicarboxylic acid (a1) is 60 mol% or more.
[0028] <3> according to <2> The polyester adhesive composition is characterized in that it further contains a hydrolysis inhibitor (II).
[0029] <4> according to <1> or <3> The polyester-based adhesive composition is characterized in that the content of the hydrolysis inhibitor (II) is 0.01 to 10 parts by weight based on 100 parts by weight of the polyester-based resin (I).
[0030] <5> according to <1> , <3> or <4> The polyester-based adhesive composition is characterized in that the weight average molecular weight of the hydrolysis inhibitor (II) is 500 or more.
[0031] <6> according to <1> , <3> , <4> or <5> The polyester-based adhesive composition is characterized in that the hydrolysis inhibitor (II) is a compound containing a carbodiimide group.
[0032] <7> according to <1> ~ <6> The polyester-based adhesive composition described above is characterized by further comprising a crosslinking agent (III).
[0033] <8> A polyester adhesive, characterized in that it is <7> The polyester adhesive composition is cross-linked by a cross-linking agent (III).
[0034] <9> An adhesive sheet, characterized in that it has an adhesive layer, wherein the adhesive layer contains <8> The polyester adhesive.
[0035] <10> according to <9> The pressure-sensitive adhesive sheet is characterized by comprising a substrate, and the pressure-sensitive adhesive layer is provided on at least one side of the substrate.
[0036] <11> according to <9> The adhesive sheet is characterized in that it is a substrate-free type having no substrate.
[0037] <12> according to <9> ~ <11> The pressure-sensitive adhesive sheet described above is used for bonding optical components.
[0038] <13> An optical component with an adhesive layer, characterized in that it has: <8> An adhesive layer of the polyester-based adhesive; and an optical member.
[0039] Effects of the Invention
[0040] According to the present invention, a polyester-based pressure-sensitive adhesive composition can be provided that can provide a pressure-sensitive adhesive having a high level of blister resistance even when exposed to a high-temperature, high-humidity environment.
[0041] The adhesive can be suitably used for bonding optical members, and is particularly suitably used for bonding optical members formed of a plastic material. DETAILED DESCRIPTION
[0042] Hereinafter, the present invention will be described in detail, but these are merely examples of preferred embodiments, and the present invention is not limited to these contents.
[0043] It should be noted that in the present invention, the term "carboxylic acid" includes carboxylic acid derivatives such as carboxylates, carboxylic anhydrides, carboxylic acid halides, and carboxylic acid esters in addition to carboxylic acids, and these carboxylic acid derivatives are referred to as "ester-forming derivatives".
[0044] In addition, the same applies to specific carboxylic acids such as isophthalic acid.
[0045] In the present invention, the term "sheet" conceptually includes sheets, films, and tapes.
[0046] <Polyester-based adhesive composition>
[0047] The polyester adhesive composition of the present invention is a polyester adhesive composition containing a polyester resin (I), wherein the polyester resin (I) is the following polyester resin (I-α) or polyester resin (I-β).
[0048] The polyester-based adhesive composition of the present invention is the following (1) or (2).
[0049] (1) A polyester adhesive composition comprising a polyester resin (I-α) having a glass transition temperature of -20 to +30°C and a hydrolysis inhibitor (II).
[0050] (2) A polyester adhesive composition comprising a polyester resin (I-β) having a glass transition temperature of -20 to +30°C and being obtained from a polycarboxylic acid component (A) containing an aromatic dicarboxylic acid (a1) at a content ratio of 50 mol % or more and a polyol component (B) containing a diol compound (b1) having a hydrocarbon group in a side chain, wherein the content ratio of isophthalic acid relative to the total amount of the aromatic dicarboxylic acid (a1) is 60 mol % or more.
[0051] In addition, the polyester-based resin (I-α) includes the polyester-based resin (I-β), but is not limited thereto.
[0052] [Polyester resin (I)]
[0053] The glass transition temperature of the polyester resin (I) (i.e., polyester resin (I-α) or polyester resin (I-β)) used in the present invention must be -20 to +30°C, preferably -15 to +25°C, more preferably -10 to +20°C, further preferably -8 to +15°C, and particularly preferably -5 to +10°C.
[0054] If the glass transition temperature exceeds the upper limit, the polyester resin (I) loses its flexibility, the initial adhesion of the adhesive (adhesion when attached to an adherend) decreases, and it becomes difficult to exert sufficient adhesive strength with a pressure of the order of finger pressure, thereby reducing workability.
[0055] If the glass transition temperature is lower than the lower limit, the cohesive force of the pressure-sensitive adhesive decreases, and floating and peeling are likely to occur, so that the object of the present invention cannot be achieved.
[0056] The glass transition temperature (Tg) of the polyester resin (I) is a value measured using a differential scanning calorimeter DSC Q20 manufactured by TA Instruments Co., Ltd. The measurement temperature range is -90°C to +100°C, and the temperature increase rate is 10°C / min.
[0057] The polyester resin (I) used in the present invention is preferably obtained by copolymerizing (polycondensing) copolymerization components including a polycarboxylic acid component (A) and a polyol component (B) as constituent raw materials.
[0058] (Polycarboxylic acid component (A))
[0059] Examples of the polycarboxylic acid component (A) include dicarboxylic acids such as aromatic dicarboxylic acids (a1), aliphatic dicarboxylic acids, and alicyclic dicarboxylic acids, and polycarboxylic acids having a valence of three or more.
[0060] As an aromatic dicarboxylic acid (a1), isophthalic acid, terephthalic acid, benzylmalonic acid, oxalic acid, 4,4'-diphenyl ether dicarboxylic acid, naphthalene dicarboxylic acid etc. are mentioned, for example.
[0061] Examples of the aliphatic dicarboxylic acid include malonic acid, dimethylmalonic acid, succinic acid, glutaric acid, adipic acid, trimethyladipic acid, pimelic acid, 2,2-dimethylglutaric acid, azelaic acid, sebacic acid, fumaric acid, maleic acid, itaconic acid, thiodipropionic acid, and diglycolic acid.
[0062] Examples of the alicyclic dicarboxylic acid include 1,3-cyclopentanedicarboxylic acid, 1,2-cyclohexanedicarboxylic acid, 1,3-cyclopentanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 2,5-norbornanedicarboxylic acid, and adamantanedicarboxylic acid.
[0063] Examples of the trivalent or higher polyvalent carboxylic acid include trimellitic acid, pyromellitic acid, adamantanetricarboxylic acid, and trimesic acid.
[0064] These may be used alone or in combination of two or more.
[0065] In the present invention, the polycarboxylic acid component (A) preferably contains 50 mol% or more of the aromatic dicarboxylic acid (a1), more preferably 55 to 100 mol%, further preferably 55 to 90 mol%, particularly preferably 60 to 85 mol%, and particularly preferably 60 to 80 mol%.
[0066] If the content ratio is too low, the cohesive force of the pressure-sensitive adhesive decreases, and floating and peeling tend to occur easily.
[0067] On the other hand, if the content ratio is too high, the flexibility of the polyester resin (I) is lost, and the initial adhesion of the adhesive tends to decrease.
[0068] Furthermore, in the present invention, the aromatic dicarboxylic acid (a1) contains isophthalic acid, and the content ratio of isophthalic acid relative to the entire aromatic dicarboxylic acid (a1) is preferably 60 mol% or more, more preferably 62 mol% or more, further preferably 65 mol% or more, particularly preferably 70 mol% or more, and most preferably 80 mol% or more.
[0069] If the content ratio is too low, the crystallinity of the polyester resin (I) increases, and the solvent solubility tends to decrease.
[0070] In the present invention, as the polycarboxylic acid component (A) other than the above-mentioned aromatic dicarboxylic acid (a1), from the viewpoint of improving the initial adhesion of the adhesive, an aliphatic dicarboxylic acid having a carbon number (including the carbon of the carboxyl group) of 4 or more is preferred, and an aliphatic dicarboxylic acid having a carbon number (including the carbon of the carboxyl group) of 9 to 12, such as azelaic acid and sebacic acid, is more preferred.
[0071] In addition, from the viewpoint of imparting a sticky feeling, it is preferred to contain an aliphatic dicarboxylic acid, particularly preferably an aliphatic dicarboxylic acid having 4 to 12 carbon atoms (including carbon atoms in the carboxyl group), and further preferably sebacic acid.
[0072] The content of the aliphatic dicarboxylic acid is preferably less than 50 mol %, particularly preferably 10 to 45 mol %, and further preferably 20 to 45 mol %, based on the entire polycarboxylic acid component (A).
[0073] If the content ratio is too low, the glass transition temperature of the polyester resin (I) becomes high and sufficient adhesive strength tends to be unable to be obtained. If the content ratio is too high, the bonding component becomes less and the adhesive strength to a polar adherend tends to decrease.
[0074] In the present invention, a trivalent or higher polycarboxylic acid may be used for the purpose of increasing branch points in the polyester resin (I), and trimellitic acid is preferably used because it is less likely to cause gelation during production.
[0075] The content ratio of the above-mentioned trivalent or higher polycarboxylic acid is preferably 10 mol % or less, more preferably 0.1 to 5 mol % relative to the total polycarboxylic acid component (A) from the perspective of the cohesive force of the adhesive. If the above-mentioned content ratio is too high, there is a tendency for the polyester resin (I) to gel easily during production.
[0076] (Polyol component (B))
[0077] In the present invention, the polyol component (B) preferably contains a diol compound (b1) having a hydrocarbon group in a side chain.
[0078] Examples of the diol compound (b1) having a hydrocarbon group in a side chain include dipropylene glycol, 2,4-dimethyl-2-ethylhexane-1,3-diol, 2-methyl-1,3-propanediol, 2,2-dimethyl-1,3-propanediol (neopentyl glycol), 2-methyl-2-ethyl-1,3-propanediol, 2-ethyl-2-butyl-1,3-propanediol, 2-ethyl-2-isobutyl-1,3-propanediol, Aliphatic diols with branched structures such as 3-propylene glycol, 1,3-butanediol, 3-methyl-1,5-pentanediol, and 2,2,4-trimethyl-1,6-hexanediol; alicyclic diols such as 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, spirodiol, tricyclodecane dimethanol, adamantanediol, and 2,2,4,4-tetramethyl-1,3-cyclobutanediol.
[0079] These may be used alone or in combination of two or more.
[0080] Among them, diol compounds having a hydrocarbon group having 1 to 6 carbon atoms, particularly 1 to 4 carbon atoms, are preferred, and neopentyl glycol and 2-methyl-2-ethyl-1,3-propanediol are more preferred, from the viewpoint of being less likely to cause crystallization while maintaining mechanical strength and heat resistance.
[0081] The content of the diol compound (b1) having a hydrocarbon group in a side chain is preferably 5 mol% or more, more preferably 15 to 90 mol%, and even more preferably 30 to 80 mol%, based on the entire polyol component (B).
[0082] If the content is too low, the polyester resin (I) will crystallize and the initial adhesive strength of the adhesive will tend to decrease. If the content is too high, the reactivity of the polyester resin (I) during production will tend to decrease.
[0083] In addition, examples of the polyol component (B) other than the diol compound (b1) having a hydrocarbon group in a side chain used in the present invention include diols such as linear aliphatic diols and aromatic diols, and trivalent or higher polyols.
[0084] Examples of the linear aliphatic diol include ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, polytetramethylene glycol, propylene glycol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol and other linear aliphatic diols and ethylene oxide and propylene oxide adducts thereof.
[0085] Examples of the aromatic diol include aromatic diols such as 4,4′-dihydroxydiphenyl sulfide, 4,4′-dihydroxydiphenylmethane, bisphenol S, bisphenol A, bisphenol fluorene, 4,4′-dihydroxybiphenyl, o-dihydroxybenzene, m-dihydroxybenzene, p-dihydroxybenzene, 2,5-naphthalene diol, and p-xylene diol, and ethylene oxide and propylene oxide adducts thereof.
[0086] Examples of the trivalent or higher polyol include pentaerythritol, dipentaerythritol, tripentaerythritol, glycerin, trimethylolpropane, trimethylolethane, 1,3,6-hexanetriol, and adamantanetriol.
[0087] These may be used alone or in combination of two or more.
[0088] Among them, linear aliphatic diols are preferably used in terms of excellent adhesive strength, and diethylene glycol, 1,4-butanediol, 1,5-pentanediol, and 1,6-hexanediol are particularly preferred. 1,4-butanediol and 1,6-hexanediol are further preferred in terms of lowering the crystallinity of the polyester resin (I) and achieving better adhesive strength.
[0089] The content of the linear aliphatic diol is preferably 5 to 95 mol %, more preferably 10 to 85 mol %, and even more preferably 20 to 70 mol %, based on the entire polyol component (B).
[0090] If the content ratio is too high, the polyester resin (I) will crystallize and the initial adhesive strength of the adhesive will tend to decrease. If the content ratio is too low, the reactivity of the polyester resin (I) during production will tend to decrease.
[0091] In the present invention, from the viewpoint of forming a reaction site with the crosslinking agent (III) described later in the polyester resin (I) and improving the cohesive force, it is preferred to use a trivalent or higher polyol, and among them, trimethylolpropane is preferably used because it is less likely to generate gel.
[0092] The content of the trivalent or higher polyol is preferably 10 mol% or less, more preferably 0.1 to 5 mol%, based on the entire polyol component (B).
[0093] If the content ratio is too high, the polyester resin (I) will gel during production, which tends to make production difficult.
[0094] (Manufacturing method)
[0095] The polyester resin (I) used in the present invention can be produced, for example, by subjecting a polycarboxylic acid component (A) and a polyol component (B) to a polycondensation reaction in the presence of a catalyst by a known method.
[0096] At this time, as the mixing ratio of the polycarboxylic acid component (A) and the polyol component (B), the polyol component (B) is preferably 1 to 2 equivalents, particularly preferably 1.1 to 1.7 equivalents per 1 equivalent of the polycarboxylic acid component (A). If the content ratio of the polyol component (B) is too low, the acid value becomes high and there is a tendency that it becomes difficult to increase the molecular weight. If the content ratio of the polyol component (B) is too high, there is a tendency that the yield decreases.
[0097] In the polycondensation reaction, first, the esterification reaction is carried out, and then the polycondensation reaction is carried out.
[0098] Examples of the catalyst used in the esterification reaction include titanium-based catalysts such as tetraisopropyl titanate and tetrabutyl titanate, antimony-based catalysts such as antimony trioxide, germanium-based catalysts such as germanium dioxide, zinc acetate, manganese acetate, dibutyltin oxide, etc. These catalysts may be used alone or in combination of two or more.
[0099] Among them, from the viewpoint of the balance between the catalytic activity and the color tone, for example, antimony trioxide, tetrabutyl titanate, germanium dioxide, and zinc acetate are preferably used.
[0100] The amount of the catalyst blended is preferably 1 to 10,000 ppm, more preferably 10 to 5,000 ppm, and even more preferably 10 to 3,000 ppm, relative to the polycarboxylic acid component (A).
[0101] If the amount is too small, the polymerization reaction tends not to proceed sufficiently, while if it is too large, there is no advantage of shortening the reaction time and a side reaction tends to occur easily.
[0102] The reaction temperature during the esterification reaction is preferably 160 to 280°C, more preferably 180 to 270°C, and further preferably 200 to 260°C.
[0103] If the reaction temperature is too low, the reaction tends not to proceed sufficiently, and if it is too high, side reactions such as decomposition tend to occur. The reaction pressure may be normal pressure.
[0104] The reaction time of the esterification reaction is preferably 1 to 48 hours, more preferably 1.5 to 24 hours, and even more preferably 2 to 12 hours.
[0105] An esterification reaction is carried out, followed by a polycondensation reaction.
[0106] As reaction conditions for the polycondensation reaction, it is preferred that the same catalyst as that used in the esterification reaction is further blended in an equal amount, the reaction temperature is preferably 220 to 280°C (more preferably 230 to 270°C), the reaction system is gradually depressurized, and the reaction is finally carried out at below 5 hPa.
[0107] If the reaction temperature is too low, the reaction tends not to proceed sufficiently, while if it is too high, side reactions such as decomposition tend to occur easily.
[0108] The reaction time of the polycondensation reaction is preferably 1 to 48 hours, more preferably 1.5 to 24 hours, and even more preferably 2 to 12 hours.
[0109] (physical properties)
[0110] The number average molecular weight of the polyester resin (I) used in the present invention is preferably 5,000 or more, more preferably 10,000 to 150,000, and even more preferably 15,000 to 80,000.
[0111] If the number average molecular weight is too low, sufficient cohesive force as an adhesive cannot be obtained, and heat resistance and mechanical strength tend to be reduced. If the number average molecular weight is too high, flexibility is lost and the initial adhesion of the adhesive tends to decrease.
[0112] It should be noted that the number average molecular weight in this specification refers to the number average molecular weight converted based on the standard polystyrene molecular weight, and is measured by high performance liquid chromatography (manufactured by Tosoh Corporation, "HLC-8320GPC") using two columns in series: TSKgel SuperMultipore HZ-M (exclusion limit molecular weight: 2×10 6 , theoretical plate number: 16000 stages / plate, filler material: styrene-divinylbenzene copolymer, filler particle size: 4 μm).
[0113] The acid value of the polyester resin (I) used in the present invention is preferably 10 mgKOH / g or less, more preferably 5 mgKOH / g or less, further preferably 1 mgKOH / g or less, particularly preferably 0.5 mgKOH / g or less.
[0114] If the acid value is too high, the adhesive layer formed from the polyester adhesive composition of the present invention is hydrolyzed, and the durability tends to be reduced. In addition, when one surface of the adhesive layer is formed into a metal oxide thin film layer, corrosion occurs, and the conductivity of the metal oxide film tends to be reduced.
[0115] The acid value of the polyester resin (I) is determined by dissolving 10 g of the polyester resin (I) in a mixed solvent of toluene and methanol at a ratio of 7 / 3 (toluene / methanol (volume ratio)) and performing neutralization titration in accordance with JIS K 0070.
[0116] In addition, in this invention, the acid value of a polyester-type resin (I) refers to the content of the carboxyl group in a resin.
[0117] [Hydrolysis inhibitor (II)]
[0118] The polyester-based adhesive composition of the present invention preferably contains a hydrolysis inhibitor (II) in addition to the polyester-based resin (I), particularly from the viewpoint of improving durability under high temperature and high humidity.
[0119] As the hydrolysis inhibitor (II), conventionally known substances can be used. Examples thereof include compounds that react and bond with the carboxylic acid terminal groups of the polycarboxylic acid component (A). Specifically, examples thereof include compounds having functional groups such as carbodiimide groups, epoxy groups, and oxazoline groups.
[0120] Among them, carbodiimide group-containing compounds are preferred because they have a high effect of eliminating the catalytic activity derived from the proton of the carboxyl terminal group.
[0121] As the carbodiimide group-containing compound, generally known carbodiimides having one or more carbodiimide groups (-N=C=N-) in the molecule can be used. In order to improve the durability under higher temperature and humidity, it is preferred to use a polycarbodiimide having two or more carbodiimide groups in the molecule, and it is particularly preferred to contain three or more, further preferably to contain five or more, and particularly preferably to contain seven or more.
[0122] It should be noted that if more than 50 are contained, the molecular structure becomes too large, which is not preferred. In addition, it is also preferred to use a high molecular weight polycarbodiimide produced by decarboxylation condensation reaction of diisocyanate in the presence of a carbodiimidization catalyst.
[0123] Examples of the high molecular weight polycarbodiimide include those obtained by subjecting the following diisocyanates to a decarboxylation condensation reaction.
[0124] Examples of the diisocyanate include 4,4'-diphenylmethane diisocyanate, 3,3'-dimethoxy-4,4'-diphenylmethane diisocyanate, 3,3'-dimethyl-4,4'-diphenylmethane diisocyanate, 4,4'-diphenyl ether diisocyanate, 3,3'-dimethyl-4,4'-diphenyl ether diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 1-methoxyphenyl-2,4-diisocyanate, isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, and tetramethylxylene diisocyanate. These may be used alone or in combination of two or more.
[0125] Such high molecular weight polycarbodiimide can be synthesized or a commercial product can be used.
[0126] Commercially available products of carbodiimide group-containing compounds include, for example, the Carbodilite (registered trademark) series manufactured by Nisshinbo Chemical Inc. Among them, Carbodilite (registered trademark) V-01, V-02B, V-03, V-05, V-07, V-09, and V-09GB are preferred in terms of excellent compatibility with organic solvents.
[0127] As the epoxy group-containing compound, glycidyl ester compounds, glycidyl ether compounds, and the like are preferred.
[0128] Specific examples of the glycidyl ester compound include glycidyl benzoate, glycidyl tert-butyl benzoate, glycidyl p-toluate, glycidyl cyclohexanecarboxylate, glycidyl nonanoate, glycidyl stearate, glycidyl laurate, glycidyl palmitate, glycidyl behenate, glycidyl versatate, glycidyl oleate, glycidyl linoleate, glycidyl linolenate, glycidyl behenate, glycidyl stearate, glycidyl terephthal ... Glycerol esters include diglycidyl isophthalate, diglycidyl phthalate, diglycidyl naphthalene dicarboxylate, diglycidyl methyl terephthalate, diglycidyl hexahydrophthalate, diglycidyl tetrahydrophthalate, diglycidyl cyclohexane dicarboxylate, diglycidyl adipic acid, diglycidyl succinate, diglycidyl sebacate, diglycidyl dodecanedioate, diglycidyl octadecane dicarboxylate, triglycidyl trimellitate, and tetraglycidyl pyromellitate. These may be used alone or in combination.
[0129] Specific examples of the glycidyl ether compound include phenyl glycidyl ether, o-phenyl glycidyl ether, 1,4-bis(β,γ-glycidyloxy)butane, 1,6-bis(β,γ-glycidyloxy)hexane, 1,4-bis(β,γ-glycidyloxy)benzene, 1-(β,γ-glycidyloxy)-2-ethoxyethane, 1-(β,γ-glycidyloxy)-2-benzyloxyethane, 2,2-bis-[p-(β,γ-glycidyloxy)phenyl]propane, 2,2-bis-(4-hydroxyphenyl)propane, and bisglycidyl polyethers obtained by reacting bisphenols such as 2,2-bis-(4-hydroxyphenyl)methane with epichlorohydrin. These may be used alone or in combination.
[0130] Examples of the oxazoline group-containing compound include bisoxazoline compounds.
[0131] Specific examples of the bisoxazoline compounds include 2,2'-bis(2-oxazoline), 2,2'-bis(4-methyl-2-oxazoline), 2,2'-bis(4,4-dimethyl-2-oxazoline), 2,2'-bis(4-ethyl-2-oxazoline), 2,2'-bis(4,4'-diethyl-2-oxazoline), 2,2'-bis(4-propyl-2-oxazoline), 2,2'-bis(4- 2,2'-bis(4-phenyl-2-oxazoline), 2,2'-bis(4-cyclohexyl-2-oxazoline), 2,2'-bis(4-benzyl-2-oxazoline), 2,2'-p-phenylenebis(2-oxazoline), 2,2'-m-phenylenebis(2-oxazoline), 2,2'-o-phenylenebis(2-oxazoline), 2,2'- p-phenylenebis(4-methyl-2-oxazoline), 2,2'-p-phenylenebis(4,4-dimethyl-2-oxazoline), 2,2'-m-phenylenebis(4-methyl-2-oxazoline), 2,2'-m-phenylenebis(4,4-dimethyl-2-oxazoline), 2,2'-ethylenebis(2-oxazoline), 2,2'-tetramethylenebis(2-oxazoline), 2,2'-hexamethylenebis(2-oxazoline), 2,2'-octamethylenebis(2-oxazoline), 2,2'-decamethylenebis(2-oxazoline), 2,2'-ethylenebis(4-methyl-2-oxazoline), 2,2'-tetramethylenebis(4,4-dimethyl-2-oxazoline), 2,2'-9,9'-diphenoxyethanebis(2-oxazoline), 2,2'-cyclohexylenebis(2-oxazoline), 2,2'-diphenylenebis(2-oxazoline), etc. These may be used alone or in combination.
[0132] Among them, 2,2′-bis(2-oxazoline) is preferred from the viewpoint of reactivity with polyester.
[0133] As the hydrolysis inhibitor (II), it is preferred to use one having a relatively high weight average molecular weight from the viewpoint of hydrolysis resistance and foaming resistance.
[0134] The weight average molecular weight of the hydrolysis inhibitor (II) is preferably 500 or more, more preferably 2000 or more, and even more preferably 5000 or more. The upper limit of the weight average molecular weight is usually 50,000.
[0135] If the weight average molecular weight of the hydrolysis inhibitor (II) is too small, the hydrolysis resistance and blister resistance tend to be reduced. On the other hand, if the weight average molecular weight is too large, the compatibility with the polyester resin tends to be reduced.
[0136] It should be noted that the weight average molecular weight in this specification refers to the weight average molecular weight converted based on the standard polystyrene molecular weight. The high performance liquid chromatograph (manufactured by Tosoh Corporation, "HLC-8320GPC") used two columns in series: TSKgel Super Multipore HZ-M (exclusion limit molecular weight: 2×10 6 , theoretical plate number: 16000 stages / plate, filler material: styrene-divinylbenzene copolymer, filler particle size: 4 μm).
[0137] The content of the hydrolysis inhibitor (II) is preferably 0.01 to 10 parts by weight, more preferably 0.1 to 5 parts by weight, further preferably 0.3 to 3 parts by weight, particularly preferably 0.5 to 1.5 parts by weight, based on 100 parts by weight of the polyester resin (I).
[0138] If the content is too large, compatibility with the polyester resin (I) decreases, and turbidity tends to be easily generated in the adhesive. If the content is too small, sufficient durability tends to be difficult to obtain.
[0139] In addition, the content of the hydrolysis inhibitor (II) is preferably optimized according to the acid value of the aforementioned polyester resin (I), and the molar ratio ((y) / (x)) of the total amount (y) of the functional groups of the hydrolysis inhibitor (II) in the polyester adhesive composition to the total acid value (x) of the polyester resin (I) in the polyester adhesive composition is preferably 0.5≤(y) / (x), particularly preferably 1≤(y) / (x)≤1000, and further preferably 1.5≤(y) / (x)≤100.
[0140] If the content ratio of the total amount (y) of the functional groups of the hydrolysis inhibitor (II) in the polyester-based adhesive composition to the total amount (x) of the acid value of the polyester-based resin (I) in the polyester-based adhesive composition increases, the compatibility with the polyester-based resin (I) tends to decrease, or the adhesive force, cohesive force and durability tend to decrease. If the content ratio of (y) to (x) decreases, the moisture-heat resistance tends to decrease.
[0141] Here, examples of the adhesive composition of the present invention include a polyester-based adhesive composition containing a polyester-based resin (I-α) having a glass transition temperature of -20 to +30°C and a hydrolysis inhibitor (II).
[0142] In addition, as another embodiment of the present invention, there can be cited a polyester-based adhesive composition, which contains the following polyester-based resin (I-β): its glass transition temperature is -20 to +30°C, and is obtained from a polycarboxylic acid component (A) containing an aromatic dicarboxylic acid (a1) at a content ratio of 50 mol% or more, and a polyol component (B) containing a diol compound (b1) having a hydrocarbon group in the side chain, and the content ratio of isophthalic acid relative to the total aromatic dicarboxylic acid (a1) is 60 mol% or more.
[0143] [Crosslinking agent (III)]
[0144] The polyester-based pressure-sensitive adhesive composition of the present invention preferably further contains a crosslinking agent (III).
[0145] By crosslinking the polyester resin (I) with the crosslinking agent (III), the cohesive force becomes excellent and the performance as a binder can be further improved.
[0146] The crosslinking agent (III) may be any compound having a functional group reactive with a functional group contained in the polyester resin (I), such as a hydroxyl group and / or a carboxyl group, and examples thereof include polyisocyanate compounds and polyepoxy compounds.
[0147] Among them, polyisocyanate compounds are preferred because they can achieve a good balance between the initial adhesion of the adhesive and the mechanical strength and heat resistance.
[0148] Examples of the polyisocyanate compound include tetramethylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, xylene diisocyanate, and hydrogenated xylene diisocyanate. In addition, examples include isocyanate adducts such as toluene diisocyanate adducts of trimethylolpropane, hexamethylene diisocyanate adducts, and isophorone diisocyanate adducts.
[0149] In addition, the polyisocyanate compound mentioned above may be a compound obtained by blocking the isocyanate moiety with phenol, lactam or the like.
[0150] These cross-linking agents (III) may be used alone or in combination of two or more.
[0151] The content of the crosslinking agent (III) can be appropriately selected depending on the amount of functional groups contained in the polyester resin (I), the molecular weight of the polyester resin (I) and the intended use. Generally, the crosslinking agent (III) is contained in an amount preferably so that the reactive groups contained in the crosslinking agent (III) become 0.2 to 10 equivalents, more preferably 0.5 to 8 equivalents, and even more preferably 1 to 5 equivalents, relative to 1 equivalent of the hydroxyl group and / or carboxyl group contained in the polyester resin (I).
[0152] If the equivalent number of reactive groups contained in the crosslinking agent (III) is too small, the cohesive force of the adhesive is insufficient and sufficient heat resistance may not be obtained. If it is too large, the flexibility of the adhesive decreases, the initial adhesion decreases, and sufficient adhesive force may not be exerted at a pressure of the level of finger pressing.
[0153] [Other ingredients]
[0154] The polyester adhesive composition of the present invention may contain conventionally known catalysts, catalytic inhibitors, softeners, ultraviolet absorbers, stabilizers, antistatic agents, thickeners and other additives, as well as inorganic or organic fillers, metal powders, pigments and other powders, granular additives, etc., within the range that does not impair the effects of the present invention.
[0155] Examples of the catalyst include organic metal compounds and tertiary amine compounds.
[0156] Examples of the organometallic compound include zirconium compounds, iron compounds, tin compounds, titanium compounds, lead compounds, cobalt compounds, and zinc compounds.
[0157] Examples of the zirconium-based compound include zirconium naphthenate and zirconium acetylacetonate.
[0158] Examples of the iron-based compound include iron acetylacetonate and iron 2-ethylhexanoate.
[0159] Examples of the tin compound include dibutyltin dichloride, dibutyltin oxide, and dibutyltin dilaurate.
[0160] Examples of the titanium-based compound include dibutyltitanium dichloride, tetrabutyl titanate, butoxytitanium trichloride, and the like.
[0161] Examples of the lead compound include lead oleate, lead 2-ethylhexanoate, lead benzoate, and lead naphthenate.
[0162] Examples of the cobalt-based compound include cobalt 2-ethylhexanoate and cobalt benzoate.
[0163] Examples of the zinc-based compound include zinc naphthenate and zinc 2-ethylhexanoate.
[0164] Examples of the tertiary amine compound include triethylamine, triethylenediamine, and 1,8-diazabicyclo-(5,4,0)-undecene-7.
[0165] Among them, zirconium-based compounds are preferred in terms of reaction speed and pot life of the adhesive layer.
[0166] In addition, the catalyst may be only one type or two or more types.
[0167] The content of the catalyst is preferably 0.001 to 0.1 part by weight, more preferably 0.005 to 0.08 part by weight, and even more preferably 0.01 to 0.05 part by weight, based on 100 parts by weight of the polyester resin (I).
[0168] If the content is too low, the curing speed becomes slow and a stable coating film tends to be difficult to form. If the content is too high, the pot life becomes short and coating properties tend to decrease.
[0169] The polyester-based adhesive composition of the present invention preferably contains a catalytic inhibitor in the catalyst in order to extend the pot life and improve coating properties.
[0170] Examples of catalytic inhibitors include β-ketoesters such as methyl acetoacetate, ethyl acetoacetate, octyl acetoacetate, oleyl acetoacetate, lauryl acetoacetate, and stearyl acetoacetate, and β-diketones such as acetylacetone, 2,4-hexanedione, and benzoylacetone. These are ketoenol tautomeric compounds, and by protecting the above-mentioned catalyst, the catalytic activity of the catalyst in the solution state is reduced, and the excessive viscosity increase and gelation of the adhesive composition after compounding are suppressed, thereby extending the pot life of the adhesive composition.
[0171] Among them, acetylacetone is preferably used as the catalyst inhibitor from the viewpoint of the balance between pot life and curing speed. It should be noted that these catalyst inhibitors may be used alone or in combination of two or more.
[0172] The ratio (weight ratio) of the catalytic inhibitor to the catalyst is preferably in the range of catalytic inhibitor:catalyst = 0.001:1 to 15:1, more preferably 0.005:1 to 13:1, and particularly preferably 0.01:1 to 10:1. If the content of the catalytic inhibitor is too small relative to the content of the catalyst, the pot life is short and the coating property tends to be reduced, while if it is too large, the curing speed tends to be reduced.
[0173] The polyester adhesive composition of the present invention preferably further contains an antioxidant from the viewpoint of improving heat resistance. By containing an antioxidant, the molecular weight reduction of the polyester resin (I) under a heat-resistant environment is suppressed, and the residual adhesive property on the adherend is excellent.
[0174] As the antioxidant, an antioxidant having a hindered phenol structure is preferred.
[0175] As the antioxidant having a hindered phenol structure, any appropriate antioxidant may be used as long as it is an antioxidant having a hindered phenol structure in which a group having a large steric hindrance such as a tert-butyl group is bonded to at least one of the carbon atoms adjacent to the carbon atom on the aromatic ring to which the OH group of phenol is bonded. By using such an antioxidant, the effect of suppressing the decrease in the molecular weight of the polyester resin (I) under a heat-resistant environment becomes very large.
[0176] The content of the antioxidant is preferably 0.01 to 10 parts by weight, more preferably 0.03 to 8 parts by weight, and even more preferably 0.05 to 5 parts by weight, based on 100 parts by weight of the polyester resin (I).
[0177] If the content is too small, adhesive residue on the adherend tends to be easily generated, while if it is too large, the adhesive properties tend to be reduced.
[0178] In addition to the above-mentioned additives, a small amount of impurities contained in the production raw materials of the constituent components of the adhesive may be contained.
[0179] <Polyester-based adhesive>
[0180] The polyester adhesive of the present invention is prepared by crosslinking the polyester adhesive composition of the present invention described above with a crosslinking agent (III). The crosslinking reaction with the crosslinking agent (III) can be performed by heating the adhesive composition at 20°C to 120°C.
[0181] The polyester-based binder of the present invention preferably contains substantially no acidic group, and specifically, the acid value is preferably 10 mgKOH / g or less, more preferably 1 mgKOH / g or less, and further preferably 0.1 mgKOH / g or less.
[0182] The acid value of the polyester-based binder can be determined by the same method as the acid value of the polyester-based resin (I).
[0183] <Adhesive Sheet>
[0184] The pressure-sensitive adhesive sheet of the present invention has a pressure-sensitive adhesive layer containing the polyester pressure-sensitive adhesive of the present invention.
[0185] The pressure-sensitive adhesive sheet of the present invention preferably has a substrate, and a pressure-sensitive adhesive layer is provided on at least one surface of the substrate.
[0186] Furthermore, the PSA sheet of the present invention is preferably a substrate-free PSA sheet having a PSA layer containing the polyester-based PSA of the present invention and having no substrate, from the viewpoint of excellent transparency and high adhesive strength to the thickness of the structure.
[0187] The pressure-sensitive adhesive sheet of the present invention is particularly suitable as a pressure-sensitive adhesive sheet for optical members used for bonding optical members.
[0188] The adhesive sheet of the present invention can be produced according to a known general method for producing an adhesive sheet. For example, a polyester adhesive composition containing a polyester resin (I) (polyester resin (I-α) or polyester resin (I-β)), preferably further containing a hydrolysis inhibitor (II) and a crosslinking agent (III) is applied to a substrate and dried, and aged as required, to obtain an adhesive sheet of the present invention having an adhesive layer formed from the polyester adhesive of the present invention on a substrate.
[0189] Alternatively, a substrate-free PSA sheet can be produced by forming a PSA layer on a release sheet and attaching a release sheet to the PSA layer on the opposite side.
[0190] When the obtained PSA sheet or substrate-less PSA sheet is used, the release sheet is peeled off from the PSA layer to bond the PSA layer to an adherend.
[0191] Examples of the substrate include polyester resins such as polyethylene naphthalate, polyethylene terephthalate, polybutylene terephthalate, and polyethylene terephthalate / polyethylene isophthalate copolymers; polyolefin resins such as polyethylene, polypropylene, and polymethylpentene; polyvinyl fluoride resins such as polyvinylidene fluoride and polyvinyl fluoride; polyamides such as nylon 6 and nylon 6,6; polyvinyl chloride, polyvinyl chloride / vinyl acetate copolymers, ethylene-vinyl acetate copolymers, and ethylene-vinyl acetate copolymers. Vinyl polymers such as vinyl alcohol copolymers, polyvinyl alcohol, and vinylon; cellulose resins such as cellulose triacetate and Cellophane; acrylic resins such as polymethyl methacrylate, polyethyl methacrylate, polyethyl acrylate, and polybutyl acrylate; synthetic resin sheets formed from synthetic resins such as polystyrene, polycarbonate, polyarylate, and polyimide; metal foils such as aluminum, copper, and iron; paper such as high-quality paper and cellophane; fabrics and non-woven fabrics formed from glass fibers, natural fibers, and synthetic fibers, etc.
[0192] These substrates may be used as a single layer or as a multilayer structure in which two or more types are laminated.
[0193] Among them, synthetic resin sheets formed of polyethylene terephthalate or polyimide are preferred, and polyethylene terephthalate sheets are particularly preferred in terms of excellent adhesion to the adhesive. Polyethylene terephthalate sheets having a metal thin film layer are further preferred in terms of excellent adhesion between the substrate and the adhesive, and being able to stably hold the substrate without corroding the metal thin film layer, and being able to significantly exert the effects of the adhesive sheet of the present invention having the polyester-based adhesive layer of the present invention.
[0194] It should be noted that, in the adhesive sheet of the present invention, it is most preferred to make an optical laminate as follows: it is a film in which an ITO (indium tin oxide) electrode film is formed on a PET (polyethylene terephthalate) substrate, the PET side of the film has an adhesive layer, the PET substrate and a PC (polycarbonate) film are laminated with the aid of the adhesive layer, and an acrylic film is further laminated (layer structure: ITO electrode film / PET substrate / adhesive layer / PC film / acrylic film).
[0195] As the above-mentioned release sheet, for example, materials obtained by subjecting various synthetic resin sheets, papers, cloths, nonwoven fabrics, etc. exemplified in the above-mentioned substrates to release treatment can be used, and examples thereof include silicone-based release sheets, olefin-based release sheets, fluorine-based release sheets, long-chain alkyl-based release sheets, and alkyd-based release sheets, and silicone-based release sheets are preferably used.
[0196] The thickness of the substrate is preferably 1 to 1000 μm, more preferably 2 to 500 μm, and further preferably 3 to 300 μm.
[0197] As a coating method of the above-mentioned adhesive composition, for example, a gravure roll coater, a reverse roll coater, a kiss roll coater, a dip roll coater, a bar coater, a knife coater, a spray coater or the like can be used.
[0198] As conditions for the aging treatment, the temperature is usually 20 to 70°C, preferably 30 to 50°C, and the time is usually 1 to 30 days, preferably 3 to 15 days.
[0199] Specifically, the reaction can be carried out, for example, at 23°C for 1 to 20 days, preferably at 23°C for 3 to 10 days, or at 40°C for 1 to 7 days.
[0200] As drying conditions, the drying temperature is preferably 60 to 140° C., more preferably 80 to 120° C., and the drying time is preferably 1 to 30 minutes, more preferably 2 to 5 minutes.
[0201] The thickness of the adhesive layer of the adhesive sheet of the present invention after drying is preferably 5 to 200 μm, more preferably 10 to 100 μm.
[0202] If the thickness of the adhesive layer is too thin, the adhesive strength tends to be reduced, while if it is too thick, uniform coating becomes difficult and troubles such as air bubbles entering the coating film tend to occur easily.
[0203] The thickness of the PSA layer is a value obtained by subtracting the thickness of constituent members other than the PSA layer from the thickness of the entire PSA sheet using "ID-C112B" manufactured by Mitutoyo Corporation.
[0204] The gel fraction of the pressure-sensitive adhesive layer of the pressure-sensitive adhesive sheet of the present invention is preferably 50% or more, more preferably 55 to 90%, and even more preferably 60 to 85%, from the viewpoint of durability and adhesive strength.
[0205] If the gel fraction is too low, the cohesive force decreases and the durability tends to decrease. If the gel fraction is too high, the cohesive force increases and the adhesive force tends to decrease.
[0206] In addition, since the said gel fraction becomes a target of a crosslinking degree, it is calculated by the following method, for example.
[0207] That is, an adhesive sheet (without separator) formed by forming an adhesive layer on a polymer sheet (such as a polyethylene terephthalate film) as a substrate is covered with a 200-mesh stainless steel wire mesh, immersed in toluene at 23°C for 24 hours, and the weight percentage of the insoluble adhesive component remaining in the wire mesh is taken as the gel fraction, wherein the weight of the substrate is subtracted in advance.
[0208] And then, the adhesive sheet of the present invention can be provided with a release sheet on the outside of the adhesive layer as required to protect. In addition, for the adhesive sheet in which the adhesive layer is formed on the single side of the substrate, the substrate is subjected to a peeling process on the surface opposite to the adhesive layer, thereby utilizing the peeling process surface to protect the adhesive layer.
[0209] <Optical member with adhesive layer>
[0210] The optical member with a pressure-sensitive adhesive layer of the present invention comprises a pressure-sensitive adhesive layer containing the polyester pressure-sensitive adhesive of the present invention and an optical member, and can be obtained by laminating the pressure-sensitive adhesive layer containing the polyester pressure-sensitive adhesive of the present invention on the optical member.
[0211] As optical components, for example, transparent electrode films such as ITO electrode films, organic conductive films such as polythiophene, polarizing plates, phase difference plates, elliptically polarizing plates, optical compensation films, brightness enhancement films, electromagnetic wave shielding films, near infrared absorption films, AR (anti-reflection) films, etc. can be cited.
[0212] Among them, a transparent electrode film is preferred, and an ITO electrode film is more preferred, from the viewpoint that the effects of the present invention can be significantly exhibited and high adhesive strength can be obtained.
[0213] It should be noted that the ITO electrode film is often formed as a thin film on a substrate such as glass or PET (polyethylene terephthalate).
[0214] The optical member with an adhesive layer of the present invention preferably further includes a release sheet on the surface of the adhesive layer opposite to the optical member surface, and in practical use, the release sheet is peeled off to bond the adhesive layer to an adherend.
[0215] As the release sheet, a silicone-based release sheet is preferably used.
[0216] Example
[0217] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to the following Examples unless the gist of the present invention is exceeded.
[0218] In addition, in an example, "part" and "%" are a weight basis.
[0219] [Manufacture of polyester resin]
[0220] Based on the molar ratios shown in Table 1 below, the following polyester resins (I-1) to (I-6) and (I′-1) to (I′-2) were produced.
[0221] (Production of Polyester Resin (I-1))
[0222] In a reactor equipped with a thermometer, a stirrer, a distillation tower, a nitrogen inlet pipe and a vacuum device, 219.4 parts (1.3 mol) of isophthalic acid and 218.5 parts (1.1 mol) of sebacic acid as the polycarboxylic acid component (A), 225 parts (2.2 mol) of neopentyl glycol, 108.2 parts (1.2 mol) of 1,4-butanediol, 24.7 parts (0.2 mol) of 1,6-hexanediol and 4.2 parts (0.03 mol) of trimethylolpropane as the polyol component (B), and 0.05 part of tetrabutyl titanate as a catalyst were added, the temperature was gradually increased to an internal temperature of 250° C., and an esterification reaction was carried out over 4 hours.
[0223] Thereafter, the internal temperature was raised to 260° C., 0.05 parts of tetrabutyl titanate was added as a catalyst, and the pressure was reduced to 1.33 hPa, and a polymerization reaction was carried out over 3 hours to produce a polyester resin (I-1).
[0224] The obtained polyester resin (I-1) had a number average molecular weight of 22,000 and a glass transition temperature of -18.0°C.
[0225] (Production of Polyester Resin (I-2))
[0226] In a reactor equipped with a thermometer, a stirrer, a distillation tower, a nitrogen inlet pipe and a vacuum device, 240.6 parts (1.4 mol) of isophthalic acid and 195.3 parts (1.0 mol) of sebacic acid as the polycarboxylic acid component (A), 226.3 parts (2.2 mol) of neopentyl glycol, 108.8 parts (1.2 mol) of 1,4-butanediol, 24.8 parts (0.2 mol) of 1,6-hexanediol and 4.2 parts (0.03 mol) of trimethylolpropane as the polyol component (B), and 0.05 parts of tetrabutyl titanate as a catalyst were added, the temperature was gradually increased to an internal temperature of 250° C., and an esterification reaction was carried out over 4 hours.
[0227] Thereafter, the internal temperature was raised to 260° C., 0.05 parts of tetrabutyl titanate was added as a catalyst, and the pressure was reduced to 1.33 hPa, and a polymerization reaction was carried out over 3 hours to produce a polyester resin (I-2).
[0228] The obtained polyester resin (I-2) had a number average molecular weight of 22,000 and a glass transition temperature of -11.0°C.
[0229] (Production of Polyester Resin (I-3))
[0230] In a reactor equipped with a thermometer, a stirrer, a distillation tower, a nitrogen inlet pipe and a vacuum device, 262.1 parts (1.6 mol) of isophthalic acid and 171.8 parts (0.8 mol) of sebacic acid as the polycarboxylic acid component (A), 227.5 parts (2.2 mol) of neopentyl glycol, 109.4 parts (1.2 mol) of 1,4-butanediol, 25 parts (0.2 mol) of 1,6-hexanediol and 4.2 parts (0.03 mol) of trimethylolpropane as the polyol component (B), and 0.05 parts of tetrabutyl titanate as a catalyst were added, the temperature was gradually increased to an internal temperature of 250° C., and an esterification reaction was carried out over 4 hours.
[0231] Thereafter, the internal temperature was raised to 260° C., 0.05 parts of tetrabutyl titanate was added as a catalyst, and the pressure was reduced to 1.33 hPa, and a polymerization reaction was carried out over 3 hours to produce a polyester resin (I-3).
[0232] The obtained polyester resin (I-3) had a number average molecular weight of 23,000 and a glass transition temperature of -6.3°C.
[0233] (Production of Polyester Resin (I-4))
[0234] In a reactor equipped with a thermometer, a stirrer, a distillation tower, a nitrogen inlet pipe and a vacuum device, 283.8 parts (1.7 mol) of isophthalic acid and 148.1 parts (0.7 mol) of sebacic acid as the polycarboxylic acid component (A), 228.8 parts (2.2 mol) of neopentyl glycol, 110 parts (1.2 mol) of 1,4-butanediol, 25.1 parts (0.2 mol) of 1,6-hexanediol and 4.3 parts (0.03 mol) of trimethylolpropane as the polyol component (B), and 0.05 parts of tetrabutyl titanate as a catalyst were added, the temperature was gradually increased to an internal temperature of 250° C., and an esterification reaction was carried out over 4 hours.
[0235] Thereafter, the internal temperature was raised to 260° C., 0.05 parts of tetrabutyl titanate was added as a catalyst, and the pressure was reduced to 1.33 hPa, and a polymerization reaction was carried out over 3 hours to produce a polyester resin (I-4).
[0236] The number average molecular weight of the obtained polyester resin (I-4) was 22,000 and the glass transition temperature was 1.6°C.
[0237] (Production of polyester resin (I-5))
[0238] In a reactor equipped with a thermometer, a stirrer, a distillation tower, a nitrogen inlet pipe and a vacuum device, 328 parts (2.0 mol) of isophthalic acid and 99.8 parts (0.5 mol) of sebacic acid as the polycarboxylic acid component (A), 231.3 parts (2.2 mol) of neopentyl glycol, 111.2 parts (1.2 mol) of 1,4-butanediol, 25.4 parts (0.2 mol) of 1,6-hexanediol and 4.3 parts (0.03 mol) of trimethylolpropane as the polyol component (B), and 0.05 part of tetrabutyl titanate as a catalyst were added, the temperature was gradually increased to an internal temperature of 250° C., and an esterification reaction was carried out over 4 hours.
[0239] Thereafter, the internal temperature was raised to 260° C., 0.05 parts of tetrabutyl titanate was added as a catalyst, and the pressure was reduced to 1.33 hPa, and a polymerization reaction was carried out over 3 hours to produce a polyester resin (I-5).
[0240] The obtained polyester resin (I-5) had a number average molecular weight of 23,000 and a glass transition temperature of 13.5°C.
[0241] (Production of polyester resin (I-6))
[0242] In a reactor equipped with a thermometer, a stirrer, a distillation tower, a nitrogen inlet pipe and a vacuum device, 182.5 parts (1.1 mol) of isophthalic acid, 101.4 parts (0.61 mol) of terephthalic acid and 148.1 parts (0.73 mol) of sebacic acid as the polycarboxylic acid component (A), 228.8 parts (2.2 mol) of neopentyl glycol, 111.0 parts (1.2 mol) of 1,4-butanediol, 25.1 parts (0.2 mol) of 1,6-hexanediol and 4.3 parts (0.03 mol) of trimethylolpropane as the polyol component (B) and 0.05 parts of tetrabutyl titanate as a catalyst were added, the temperature was gradually increased to an internal temperature of 250° C., and an esterification reaction was carried out over 4 hours.
[0243] Thereafter, the internal temperature was raised to 260° C., 0.05 parts of tetrabutyl titanate was added as a catalyst, and the pressure was reduced to 1.33 hPa, and a polymerization reaction was carried out over 3 hours to produce a polyester resin (I-6).
[0244] The obtained polyester resin (I-6) had a number average molecular weight of 16,000 and a glass transition temperature of 2.1°C.
[0245] (Production of Polyester Resin (I'-1))
[0246] In a reactor equipped with a thermometer, a stirrer, a distillation tower, a nitrogen inlet pipe and a vacuum device, 76.9 parts (0.5 mol) of isophthalic acid and 374.3 parts (1.9 mol) of sebacic acid as the polycarboxylic acid component (A), 216.8 parts (2.1 mol) of neopentyl glycol, 104.2 parts (1.2 mol) of 1,4-butanediol, 23.8 parts (0.2 mol) of 1,6-hexanediol and 4 parts (0.03 mol) of trimethylolpropane as the polyol component (B), and 0.05 parts of tetrabutyl titanate as a catalyst were added, the temperature was gradually increased to an internal temperature of 250° C., and an esterification reaction was carried out over 4 hours.
[0247] Thereafter, the internal temperature was raised to 260° C., 0.05 parts of tetrabutyl titanate was added as a catalyst, and the pressure was reduced to 1.33 hPa, and a polymerization reaction was carried out over 3 hours to produce a polyester resin (I′-1).
[0248] The obtained polyester resin (I'-1) had a number average molecular weight of 25,000 and a glass transition temperature of -48.5°C.
[0249] (Production of Polyester Resin (I'-2))
[0250] Into a reactor equipped with a thermometer, a stirrer, a distillation tower, a nitrogen inlet pipe and a vacuum device, 76.6 parts (0.5 mol) of isophthalic acid as the polycarboxylic acid component (A), 186.5 parts (0.9 mol) of sebacic acid, 173.6 parts (0.9 mol) of azelaic acid, 14.3 parts (0.2 mol) of ethylene glycol as the polyol component (B), 349 parts (2.4 mol) of cyclohexanedimethanol and 0.04 parts of germanium dioxide as a catalyst were added, the temperature was slowly raised to an internal temperature of 250°C, and the esterification reaction was carried out for 4 hours.
[0251] Thereafter, the internal temperature was raised to 270° C., the pressure was reduced to 1.33 hPa, and a polycondensation reaction was carried out over 3 hours to produce a polyester resin (I′-2).
[0252] The obtained polyester resin (I'-2) had a number average molecular weight of 30,000 and a glass transition temperature of -25.6°C.
[0253] [Table 1]
[0254] Table 1
[0255]
[0256] <Test Example 1>
[0257] [Production of polyester-based adhesive composition]
[0258] (Example 1-1)
[0259] The polyester resin (I-1) obtained above was diluted with ethyl acetate to a solid content concentration of 55% by weight, and 1 part (solid content) of polycarbodiimide (manufactured by Nisshinbo Chemical Inc.; trade name "Carbodilite V-07", weight average molecular weight (Mw): 6231) as a hydrolysis inhibitor and 3 parts (solid content) of trimethylolpropane / toluene diisocyanate adduct (manufactured by Tosoh Corporation; product name "CORONATE L55E") as a crosslinking agent were added and stirred and mixed to obtain a polyester adhesive composition.
[0260] (Example 1-2)
[0261] In Example 1-1, a polyester-based adhesive composition was obtained in the same manner as in Example 1-1 except that the polyester-based resin (I-1) was changed to the polyester-based resin (I-3) and the amount of the crosslinking agent was changed to 4 parts.
[0262] (Example 1-3)
[0263] In Example 1-1, a polyester-based adhesive composition was obtained in the same manner as in Example 1-1 except that the polyester-based resin (I-1) was changed to the polyester-based resin (I-4), the amount of the hydrolysis inhibitor was changed to 0.1 parts, and the amount of the crosslinking agent was changed to 4 parts.
[0264] (Examples 1-4)
[0265] In Example 1-1, a polyester-based adhesive composition was obtained in the same manner as in Example 1-1 except that the polyester-based resin (I-1) was changed to the polyester-based resin (I-4), the amount of the hydrolysis inhibitor was changed to 0.5 parts, and the amount of the crosslinking agent was changed to 4 parts.
[0266] (Examples 1-5)
[0267] In Example 1-1, a polyester-based adhesive composition was obtained in the same manner as in Example 1-1 except that the polyester-based resin (I-1) was changed to the polyester-based resin (I-4) and the amount of the crosslinking agent was changed to 4 parts.
[0268] (Examples 1-6)
[0269] In Example 1-1, a polyester-based adhesive composition was obtained in the same manner as in Example 1-1 except that the polyester-based resin (I-1) was changed to a polyester-based resin (I-4), the hydrolysis inhibitor was changed to a polycarbodiimide ("Carbodilite V-09GB" manufactured by Nisshinbo Chemical Inc., weight average molecular weight (Mw): 5951), and the amount of the cross-linking agent was changed to 4 parts.
[0270] (Examples 1-7)
[0271] In Example 1-1, a polyester-based adhesive composition was obtained in the same manner as in Example 1-1 except that the polyester-based resin (I-1) was changed to the polyester-based resin (I-5) and the amount of the crosslinking agent was changed to 4 parts.
[0272] (Comparative Example 1-1)
[0273] In Example 1-1, a polyester-based adhesive composition was obtained in the same manner as in Example 1-1 except that the polyester-based resin (I-1) was changed to the polyester-based resin (I′-1).
[0274] (Comparative Example 1-2)
[0275] In Example 1-1, a polyester-based adhesive composition was obtained in the same manner as in Example 1-1 except that the polyester-based resin (I-1) was changed to the polyester-based resin (I′-2).
[0276] [Manufacturing of adhesive film]
[0277] Each polyester adhesive composition obtained above was applied onto a 38 μm thick PET (polyethylene terephthalate) separator using an applicator and dried at 100° C. for 4 minutes to obtain an adhesive sheet having an adhesive layer with a thickness of 50 μm.
[0278] Next, the surface of the obtained PSA composition layer was covered with a 38 μm thick PET separator having a different release strength from the above separator, and aged at 40° C. for 4 days to obtain a PSA film with separators on both sides.
[0279] [Evaluation of adhesive sheets]
[0280] (Adhesion at high temperature)
[0281] The separator on one side was peeled off from the PSA layer of each of the PSA films with separators on both sides obtained above, and the PSA layer was transferred to a PET film (100 μm) to prepare a PSA sheet for evaluation.
[0282] The separator on the other side of the adhesive layer of the adhesive sheet for evaluation obtained above was peeled off, and the adhesive layer was attached to a polycarbonate plate ("STELLA" manufactured by Mitsubishi Plastics Co., Ltd.), and pressure-bonded for 20 minutes at 0.5 MPa and 50° C. using a cylindrical liquid crystal pressure degassing device ("YK-350S" manufactured by Kurihara Seisakusho). Thereafter, the 180-degree peel strength (N / 25 mm) was measured at a peeling speed of 300 mm / min at 85° C. using a tensile testing machine with a constant temperature bath ("Autograph AGS-H 500N" manufactured by Shimadzu Corporation). The results are shown in Table 2.
[0283] (Blistering resistance)
[0284] Another separator was peeled off from the adhesive layer of the adhesive sheet for evaluation obtained above, and the adhesive layer was adhered to a polycarbonate plate ("STELLA" manufactured by Mitsubishi Plastics Corporation), and pressed at 0.5 MPa and 50°C for 20 minutes to prepare a test piece having the structure of "PC plate / polyester adhesive layer / PET film".
[0285] After that, the test piece was loaded in a constant temperature and humidity chamber at 85°C / 85% for 24 hours, and the appearance of the test piece after loading (presence of blistering) was visually checked. The blistering resistance was evaluated based on the following criteria. The results are shown in Table 2.
[0286] ◎: No foaming, no change in appearance.
[0287] ○: The area of the foamed portion is about 1 / 4 or less of the area of the test piece.
[0288] △: The area of the foamed portion is more than about 1 / 4 and less than about half of the area of the test piece.
[0289] ×: The area of the foamed portion is approximately more than half of the area of the test piece.
[0290] [Table 2]
[0291] Table 2
[0292]
[0293] The above results show that the adhesive sheet having an adhesive layer formed using the adhesive composition of Examples 1-1 to 1-7 containing a polyester resin having a glass transition temperature within the desired range and a hydrolysis inhibitor has excellent adhesive strength even at high temperatures, and when the adhesive layer is exposed to high temperature and high humidity, there is little foaming and the blistering resistance is very excellent.
[0294] On the other hand, it is found that in Comparative Examples 1-1 and 1-2 using polyester resins whose glass transition temperatures are not within the desired range, the adhesive strength at high temperatures is low and the blister resistance is not satisfactory.
[0295] <Test Example 2>
[0296] [Production of polyester-based adhesive composition]
[0297] (Example 2-1)
[0298] The polyester resin (I-1) obtained above was diluted with ethyl acetate to a solid content concentration of 55% by weight, and 1 part (solid content) of a hydrolysis inhibitor (manufactured by Nisshinbo Chemical Inc.; trade name "Carbodilite V-07") and 3 parts (solid content) of a trimethylolpropane / toluene diisocyanate adduct (manufactured by Tosoh Corporation; product name "CORONATE L55E") as a cross-linking agent were added and stirred and mixed to obtain a polyester adhesive composition.
[0299] (Example 2-2)
[0300] In Example 2-1, a polyester-based adhesive composition was obtained in the same manner as in Example 2-1 except that the polyester-based resin (I-1) was changed to the polyester-based resin (I-2) and the amount of the crosslinking agent was changed to 4 parts.
[0301] (Example 2-3)
[0302] In Example 2-1, a polyester-based adhesive composition was obtained in the same manner as in Example 2-1 except that the polyester-based resin (I-1) was changed to the polyester-based resin (I-3) and the amount of the crosslinking agent was changed to 4 parts.
[0303] (Example 2-4)
[0304] In Example 2-1, a polyester-based adhesive composition was obtained in the same manner as in Example 2-1 except that the polyester-based resin (I-1) was changed to the polyester-based resin (I-4) and the amount of the crosslinking agent was changed to 4 parts.
[0305] (Example 2-5)
[0306] In Example 2-1, a polyester-based adhesive composition was obtained in the same manner as in Example 2-1 except that the polyester-based resin (I-1) was changed to the polyester-based resin (I-5) and the amount of the crosslinking agent was changed to 4 parts.
[0307] (Example 2-6)
[0308] The polyester resin (I-6) obtained above was diluted with ethyl acetate to a solid content concentration of 55% by weight. To 100 parts (solid content) of the polyester resin (I-6) solution, 0.7 parts (solid content) of a hydrolysis inhibitor (manufactured by Nisshinbo Chemical Inc.; trade name "Carbodilite V-09GB"), 5.0 parts (solid content) of a trimethylolpropane / toluene diisocyanate adduct (manufactured by Tosoh Corporation; product name "CORONATE L55E") as a crosslinking agent, and a zirconium compound (manufactured by MATSUMOTO FINE CHEMICAL CO. LTD.; product name "ORGATIX VIZO" as a catalytic inhibitor of a urethanization catalyst diluted with acetylacetone to a solid content concentration of 1% were added. ZC-150”) 0.01 part (solid content ratio) and 0.1 part (solid content ratio) of a hindered phenol antioxidant (manufactured by BASF Corporation; product name “Irganox 1010”) as an antioxidant were added, stirred and mixed to obtain a polyester-based adhesive composition.
[0309] (Comparative Example 2-1)
[0310] In Example 2-1, a polyester-based adhesive composition was obtained in the same manner as in Example 2-1 except that the polyester-based resin (I-1) was changed to the polyester-based resin (I′-1).
[0311] (Comparative Example 2-2)
[0312] In Example 2-1, a polyester-based adhesive composition was obtained in the same manner as in Example 2-1 except that the polyester-based resin (I-1) was changed to the polyester-based resin (I′-2).
[0313] [Manufacturing of adhesive film]
[0314] Each polyester adhesive composition obtained above was applied onto a 38 μm thick PET (polyethylene terephthalate) separator using an applicator and dried at 100° C. for 4 minutes to obtain an adhesive sheet having an adhesive layer with a thickness of 50 μm.
[0315] Next, the surface of the obtained PSA composition layer was covered with a 38 μm thick PET separator having a different release strength from the above separator, and aged at 40° C. for 4 days to obtain a PSA film with separators on both sides.
[0316] [Evaluation of adhesive sheets]
[0317] (Adhesion at high temperature)
[0318] The separator on one side was peeled off from the PSA layer of each of the PSA films with separators on both sides obtained above, and the PSA layer was transferred to a PET film (100 μm) to prepare a PSA sheet for evaluation.
[0319] The separator on the other side was peeled off from the adhesive layer of the adhesive sheet for evaluation obtained above, and the adhesive layer was attached to a polyester plate ("STELLA" manufactured by Mitsubishi Plastics Co., Ltd.), and pressure-bonded for 20 minutes at 0.5 MPa and 50° C. using a cylindrical liquid crystal pressure degassing device ("YK-350S" manufactured by Kurihara Seisakusho). Thereafter, the 180-degree peel strength (N / 25 mm) at a peeling speed of 300 mm / min at 85° C. was measured using a tensile testing machine with a thermostatic bath ("Autograph AGS-H 500N" manufactured by Shimadzu Corporation). The results are shown in Table 3.
[0320] (Blistering resistance)
[0321] Another separator was peeled off from the adhesive layer of the adhesive sheet for evaluation obtained above, and the adhesive layer was adhered to a polycarbonate plate ("STELLA" manufactured by Mitsubishi Plastics Corporation), and pressed at 0.5 MPa and 50°C for 20 minutes to prepare a test piece having the structure of "PC plate / polyester adhesive layer / PET film".
[0322] After that, the test piece was loaded in a constant temperature and humidity chamber at 85°C / 85% for 24 hours, and the appearance of the test piece after loading (presence of blistering) was visually checked. The blistering resistance was evaluated based on the following criteria. The results are shown in Table 3.
[0323] ◎: No foaming, no change in appearance.
[0324] ○: The area of the foamed portion is about 1 / 4 or less of the area of the test piece.
[0325] △: The area of the foamed portion is more than about 1 / 4 and less than about half of the area of the test piece.
[0326] ×: The area of the foamed portion is approximately more than half of the area of the test piece.
[0327] [Table 3]
[0328] Table 3
[0329]
[0330] From the above results, it can be seen that the adhesive sheet having an adhesive layer formed using the adhesive composition of Examples 2-1 to 2-6 containing a polyester resin (I) having a glass transition temperature within the desired range and formed of a specific composition has excellent adhesive strength even at high temperatures, and the adhesive layer has little foaming when exposed to high temperature and high humidity, and has very excellent foaming resistance.
[0331] On the other hand, in Comparative Examples 2-1 and 2-2 using polyester resins whose glass transition temperatures were not within the desired range, it was found that the adhesive strength at high temperatures was low and the blister resistance was not satisfactory.
[0332] The present invention is described in detail and with reference to specific embodiments, but it is obvious to those skilled in the art that various changes and modifications can be made without departing from the concept and scope of the present invention. This application is based on Japanese patent application (Special Application 2016-257101) filed on December 28, 2016, Japanese patent application (Special Application 2017-102073) filed on May 23, 2017, Japanese patent application (Special Application 2017-232862) filed on December 4, 2017, and Japanese patent application (Special Application 2017-232863) filed on December 4, 2017, and the contents are introduced herein as reference.
Claims
1. A polyester adhesive composition, characterized in that Containing a polyester resin (I), The polyester resin (I) is a polyester resin (I-β) having a glass transition temperature of not less than -20°C and less than 20°C, and is obtained from a polycarboxylic acid component (A) containing an aromatic dicarboxylic acid (a1) at a content ratio of not less than 50 mol %, and a polyol component (B) containing a diol compound (b1) having a hydrocarbon group in a side chain, wherein the content ratio of isophthalic acid relative to the entire aromatic dicarboxylic acid (a1) is not less than 60 mol %.
2. The polyester adhesive composition according to claim 1, characterized in that It also contains a hydrolysis inhibitor (II).
3. The polyester adhesive composition according to claim 2, characterized in that The content of the hydrolysis inhibitor (II) is 0.01 to 10 parts by weight based on 100 parts by weight of the polyester resin (I).
4. The polyester adhesive composition according to claim 2, characterized in that: The weight average molecular weight of the hydrolysis inhibitor (II) is 500 or more.
5. The polyester adhesive composition according to claim 2, characterized in that: The hydrolysis inhibitor (II) is a compound containing a carbodiimide group.
6. The polyester adhesive composition according to claim 1 or 2, characterized in that: It also contains a cross-linking agent (III).
7. A polyester adhesive, characterized in that: The polyester adhesive composition according to claim 6 is cross-linked with a cross-linking agent (III).
8. An adhesive sheet, characterized in that: A pressure-sensitive adhesive layer is provided, wherein the pressure-sensitive adhesive layer contains the polyester pressure-sensitive adhesive according to claim 7.
9. The adhesive sheet according to claim 8, characterized in that A substrate is provided, and the adhesive layer is provided on at least one side of the substrate.
10. The adhesive sheet according to claim 9, characterized in that It is a substrate-less type having no substrate.
11. The adhesive sheet according to any one of claims 8 to 10, characterized in that It is used for bonding optical components.
12. An optical member with an adhesive layer, characterized in that: The invention comprises: a pressure-sensitive adhesive layer containing the polyester-based pressure-sensitive adhesive according to claim 7; and an optical member.
13. An optical member comprising a substrate, The substrate is at least one selected from the group consisting of glass and polyethylene terephthalate, The optical component is an ITO electrode film. The optical component further comprises an adhesive layer. This optical member is formed by laminating the ITO electrode film, the substrate, and the adhesive layer in this order.
14. The optical component according to claim 13, wherein The adhesive layer is a polyester adhesive composition containing a polyester resin (I), The polyester resin (I) is a polyester resin (I-β) having a glass transition temperature of not less than -20°C and less than 20°C, and is obtained from a polycarboxylic acid component (A) containing an aromatic dicarboxylic acid (a1) at a content ratio of not less than 50 mol %, and a polyol component (B) containing a diol compound (b1) having a hydrocarbon group in a side chain, wherein the content ratio of isophthalic acid relative to the entire aromatic dicarboxylic acid (a1) is not less than 60 mol %.
15. The optical component according to claim 13, wherein The substrate is polyethylene terephthalate.
16. An optical laminate, which is the optical member according to claim 15, further laminated with a polycarbonate film and an acrylic film, The optical laminate is formed by laminating the ITO electrode film, the substrate, the adhesive layer, the polycarbonate film, and the acrylic film in this order.
17. An adhesive sheet comprising an adhesive layer and a release sheet, The adhesive sheet does not have a substrate, The adhesive sheet is formed by laminating a release sheet, an adhesive layer, and a release sheet in this order.
18. The adhesive sheet according to claim 17, wherein the adhesive layer is a polyester adhesive composition containing a polyester resin (I). The polyester resin (I) is a polyester resin (I-β) having a glass transition temperature of not less than -20°C and less than 20°C, and is obtained from a polycarboxylic acid component (A) containing an aromatic dicarboxylic acid (a1) at a content ratio of not less than 50 mol %, and a polyol component (B) containing a diol compound (b1) having a hydrocarbon group in a side chain, wherein the content ratio of isophthalic acid relative to the entire aromatic dicarboxylic acid (a1) is not less than 60 mol %.
19. The adhesive sheet according to claim 18, wherein The release sheet is a silicone-based release sheet.
Citation Information
Patent Citations
Polyester-based adhesive and its adhesive sheet
JP2007045914A
Pressure-sensitive adhesive composition and utilization thereof
JP2009007419A
Adhesive composition, adhesive layer, adhesive tape, and double-sided adhesive tape
JP2015134906A
Semiconductor device manufacturing method
JP2017102073A